Carboxylic acids and light interact to affect nanoceria stability and dissolution in acidic aqueous environments - Hancock, Matthew L.; Grulke, Eric A.; Yokel, Robert A. (Beilstein Journal of Nanotechnology, 2023)
Cerium atoms on the surfaces of nanoceria (i.e., cerium oxide in the form of nanoparticles) can store or release oxygen, cycling between Ce3+ and Ce4+; therefore, they can cause or relieve oxidative stress within living systems. Nanoceria dissolution occurs in acidic environments. Nanoceria stabilization is a known problem even during its synthesis; in fact, a carboxylic acid, namely citric acid, is used in many synthesis protocols. Citric acid adsorbs onto nanoceria surfaces, limiting particle formation and creating stable dispersions with extended shelf life. To better understand factors influencing the fate of nanoceria, its dissolution and stabilization have been previously studied in vitro using acidic aqueous environments. Nanoceria agglomerated in the presence of some carboxylic acids over 30 weeks, and degraded in others, at pH 4.5 (i.e., the pH value in phagolysosomes). Plants release carboxylic acids, and cerium carboxylates are found in underground and aerial plant parts. To further test nanoceria stability, suspensions were exposed to light and dark conditions, simulating plant environments and biological systems. Light induced nanoceria agglomeration in the presence of some carboxylic acids. Nanoceria agglomeration did not occur in the dark in the presence of most carboxylic acids. Light initiates free radicals generated by ceria nanoparticles. Nanoceria completely dissolved in the presence of citric, malic, and isocitric acid when exposed to light, attributed to nanoceria dissolution, release of Ce3+ ions, and formation of cerium coordination complexes on the ceria nanoparticle surface that inhibit agglomeration. Key functional groups of carboxylic acids that prevented nanoceria agglomeration were identified. A long carbon chain backbone containing a carboxylic acid group geminal to a hydroxy group in addition to a second carboxylic acid group may optimally complex with nanoceria. The results provide mechanistic insight into the role of carboxylic acids in nanoceria dissolution and its fate in soils, plants, and biological systems.
Keywords: acidic aqueous environments; carboxylic acids; electron microscopy; environmentally mediated dissolution; nanoceria